2015
DOI: 10.1007/s00467-015-3074-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disease duration on quality of life in children with nephrotic syndrome: a Midwest Pediatric Nephrology Consortium study

Abstract: Background The Patient Reported Outcomes Measurement Information System (PROMIS) II is a prospective study that evaluates patient reported outcomes in pediatric chronic diseases as a measure of health-related quality of life (HRQOL). We have evaluated the influence of disease duration on HRQOL and, for the first time, compared the findings of the PROMIS measures to those of the PedsQL™ 4.0 Generic Scales (PedsQL) from the PROMIS II nephrotic syndrome (NS) longitudinal cohort. Methods This was a prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 20 publications
2
78
0
Order By: Relevance
“…D.T. Selewski, et al's study [8] shows that QOL score in the learning field increases, which means that the QOL related to learning is declined.…”
mentioning
confidence: 98%
“…D.T. Selewski, et al's study [8] shows that QOL score in the learning field increases, which means that the QOL related to learning is declined.…”
mentioning
confidence: 98%
“…Whenever possible, offer extended hours for research visits, including evenings or weekends, to minimize work or school absences for the subject and family caregiver. Alternatives to traditional study visits may include studies in which patient-reported information through text messaging, smartphones, or other home monitoring devices optimizes prospective data collection while minimizing study burden (32)(33)(34). The electronic medical record may be used to simultaneously collect clinical and research data, or collected data may be accessed for subsequent research endeavors.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…Only the QOL subscale "social function" was impaired while other domains were not affected [3]. In USA, an evaluation of QOL using PedsQL Inventory in 127 American children with prevalent NS as compared to incident NS showed poor scores in social and school performances [2].…”
Section: Discussionmentioning
confidence: 93%
“…Although 80% of these children are corticosteroid responsive, nearly half of them demonstrate a frequently relapsing or steroid-dependent course, often resulting in multiple complications, hospitalizations, or even chronic renal failure [2]. Not infrequently, NS spans a significant portion of a child's formative years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation